The Religiosity of the Indonesian Constitution: Article 29(1) and Its Interpretation - Ahmad Rofii (The Constitutional Court of the Republic of Indonesia, 2021)
This paper examines the problem of whether the inclusion of religious words in the Indonesian Constitution is tantamount to the establishment of a religious constitution. By focusing on the Constitution’s provision on “belief in the One and Only God” in Article 29(1), this paper challenges the received theory of the religiosity of the Constitution. To that end, the paper first investigates the doctrinal and historical implications of Article 29(1). Particular analysis concerns the implications of this constitutionalization for Islamic law. The Constitutional Court’s decision on interreligious marriage is critically examined as an example of how the received theory is endorsed and articulated in the case of marriage. This paper argues that Article 29(1) concerns all religions, without any implied exclusion of non-monotheistic religions. Moreover, this paper affirms what is called the Pancasila state, located between an exclusively secular state and a religious or theocratic state. This arguably makes the notion of the religiosity of the Constitution unjustified. The Constitutional Court, however, has interpreted Article 29(1) in a strongly religious sense, leading to religious supremacy and, accordingly, is contrary to how the Constitution ought to be understood.